Soundscapes of the urban past : staged sound as mediated cultural heritage - Bijsterveld, Karin (2013)
We cannot simply listen to our urban past. Yet we encounter a rich cultural heritage of city sounds presented in text, radio and film. How can such »staged sounds« express the changing identities of cities?This volume presents a collection of studies on the staging of Amsterdam, Berlin and London soundscapes in historical documents, radio plays and films, and offers insights into themes such as film sound theory and museum audio guides. In doing so, this book puts contemporary controversies on urban sound in historical perspective, and contextualises iconic presentations of cities. It addresses academics, students, and museum workers alike.With contributions by Jasper Aalbers, Karin Bijsterveld, Carolyn Birdsall, Ross Brown, Andrew Crisell, Andreas Fickers, Annelies Jacobs, Evi Karathanasopoulou, Patricia Pisters, Holger Schulze, Mark M. Smith and Jonathan Sterne.